Evaluation of Nurses’ attitudes, behaviors, and barriers toward pressure ulcer prevention in neonatal and pediatric intensive care units - Mostafa, Osama Elshahat; Zakari, Nazik M. A.; Al Salem, Marwa (Frontiers in Pediatrics, 2024)
Introduction Pressure ulcers are a significant concern in pediatric intensive care units, with prevalence rates ranging from 0.8% to 27%. They pose serious physical and psychological challenges, particularly in neonatal and pediatric intensive care units (NICU and PICU). This study explores nursing strategies, attitudes, and barriers toward pressure ulcer prevention in NICU and PICU settings. Methods Using a descriptive study design, data were collected from 80 nurses working in NICU and PICU through validated questionnaires, including a demographic profile and a pressure ulcer survey. Descriptive statistics were employed to calculate mean scores and percentages, while inferential statistics assessed associations between variables. Results The study revealed specific nursing strategies, along with significant barriers and attitudes toward pressure ulcer prevention in NICU and PICU. The total attitude mean score was 3.57, with the highest positive response (mean = 4.29) for “most pressure sores can be avoided”, and the highest negative response (mean = 3.86) for “pressure sore prevention is a low priority for me”. Among participants, 72.5% conducted risk assessments on all patients, 60% had written prevention care plans, and 76.3% implemented preventive strategies. Barriers such as staff shortages and time constraints were reported by 76.2% of nurses. Multivariate analysis indicated that nurses with more than 10 years of qualification (OR = 3.67) and permanent staff with over 10 years of employment (OR = 4.31) were significantly more likely to engage in preventive practices. The use of a pressure ulcer grading tool (OR = 2.49, P < 0.05) and participation in formal training (OR = 3.14, P < 0.05) were also positively associated with preventive practices. Discussion These findings underscore the importance of structured assessment tools, ongoing education, and the need to foster positive attitudes among nurses to effectively reduce pressure ulcer prevalence and enhance patient outcomes in NICU and PICU settings.